The Exposure to Osteoarthritic Synovial Fluid Enhances the Immunomodulatory Profile of Adipose Mesenchymal Stem Cell Secretome. (18th July 2020) - Cifù, Adriana; Domenis, Rossana; Pozzi-Mucelli, Massimo; Di Benedetto, Paolo; Causero, Araldo; Moretti, Massimo; Stevanato, Marta; Pistis, Cinzia; Parodi, Pier Camillo; Fabris, Martina; Curcio, Francesco
Abstract : Objective . Several clinical studies have proposed the infusion of adipose mesenchymal stem cells (AMSCs) as an alternative therapy for joint diseases with inflammatory components, such as osteoarthritis. Indeed, AMSCs are able to stimulate tissue repair through a paracrine activity and the interaction with the inflammatory microenvironment seems to have a critical role. Design . To reproduce the inflammatory microenvironment, AMSCs were exposed to osteoarthritic synovial fluid (SF) for 48 h and the effect of their secretome on differentiation of monocytes (M0) into macrophages M1-like and mature dendritic cells (mDCs) was evaluated. Furthermore, the effect of the secretome of AMSCs exposed to SF was evaluated on the T cell population in terms of T cell proliferation and expansion of T regulatory cells (T reg). Results . Our data show that the exposure of AMSCs to SF activates cells and promotes the release of immunosuppressive factors, which induce macrophage polarization of M0 into the M2-like phenotype and inhibit differentiation of monocytes into mature dendritic cells (mDCs). Only the secretome of exposed AMSCs was able to inhibit T cell proliferation and promote T reg expansion. Conclusions . Our results suggest that the microenvironment plays a fundamental role for the development of anti-inflammatory and immunomodulatory properties of AMSCs.